Work Overload and Turnover Intention of Junior Auditors in Greater Jakarta, Indonesia - Pradana, Andika; Salehudin, Imam (The South East Asian Journal of Management, 2015)
This paper aims to analyze how work overload influences turnover intentions of newly hired junior auditors in public accounting offices. Job satisfaction, work related stress and work life conflicts are used as mediating variables between work overload and turnover intention. This study employed 141 auditors from several accounting firms operating in the Greater Jakarta region. The sample was selected using purposive sampling. Three mediation hypotheses were tested using Structural Equation Modeling (SEM). The results show that work overload has a significant effect on increasing turnover intention through both job satisfaction and work related stress. In comparison, work overload does not influence turnover intention through work life balance. This may be due to the nature of the respondents, in which a majority of the newly hired accountants employed in this study are unmarried.